One step hydrothermal synthesis of 3D CoS2@MoS2-NG for high performance supercapacitors. (16th May 2018) - Meng, Qi; Chen, Yizhi; Zhu, Wenkun; Zhang, Ling; Yang, Xiaoyong; Duan, Tao
Abstract: A three-dimensional (3D) MoS2 coated CoS2 -nitrogen doped graphene (NG) (CoS2 @MoS2 -NG) hybrid has been synthesized by a one step hydrothermal method as supercapacitor (SC) electrode material for the first time. Such a composite consists of NG embedded with stacked CoS2 @MoS2 sheets. With a 3D skeleton, it prevents the agglomeration of CoS2 @MoS2 nanoparticles, resulting in sound conductivity, rich porous structures and a large surface area. The results indicate that CoS2 @MoS2 -NG has higher specific capacitance (198 F g −1 at 1 A g −1 ), better rate performance (with about 56.57% from 1 to 16 A g −1 ) and an improved cycle stability (with about 96.97% after 1000 cycles). It is an ideal candidate for SC electrode materials.